Fault detection, accomodation and isolation for paper mill industrial control - Apasamy, Prem Kumar (2007)
Instrument fault in industries is an interruption to industries production and maintenance. Its cause loses of production and time. As industries growing faster and rapidly, there are a need of method to detect the fault of instrument before its can disturb the production of industries. Conventional technique such as Predictive Maintenance and Run to Fail not did not give much room in term of predictability of instrument fault. Many study and research done on the fault detection technique and new technique Artificial Intelligent technique (AI) application in fault detection be come one of major studies in research. Using the parameter and variable from process and instruments, AI can be constructed and applied to view the reliability of the AI technique in the fault detection method. The predictability of AI will be measure as performance indicator of fault detection.